2010
DOI: 10.1111/j.1750-3841.2009.01446.x
|View full text |Cite
|
Sign up to set email alerts
|

Histological Contribution of Collagen Architecture to Beef Toughness

Abstract: The relationship between shear-force value and collagen architecture of connective tissue of the longissimus thoracis (LT) muscle of Japanese Black (n = 10) and Brown (Kumamoto) (n = 5) steers (body weight: 688.4 +/- 8.6 kg as average and standard error) was investigated. There were negative correlations between the shear-force value and lipid content (n = 15, R(2)= 0.3709, P < 0.01) and protein content and lipid content (n = 15, R(2)= 0.6748, P < 0.01). Shear-force value and collagen content (n = 15, R(2)= 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 20 publications
1
8
1
Order By: Relevance
“…Post‐rigor foot samples, however, were significantly firmer when evaluated by shear (34.6 N POST‐5‐300) than by TPA (8.8 N POST‐5–300). While HPP up to 500 MPa was shown to reduce shear force values in beef from 5.9 N (unprocessed control) to 4.3 N (100 MPa) and 4.9 N (500 MPa; Ichinoseki and others ), the higher shear force values observed in this study were likely due to the much higher collagen content in abalone (3.5%) compared to beef (0.29% to 0.57%); Nakamura and others ).…”
Section: Resultscontrasting
confidence: 48%
“…Post‐rigor foot samples, however, were significantly firmer when evaluated by shear (34.6 N POST‐5‐300) than by TPA (8.8 N POST‐5–300). While HPP up to 500 MPa was shown to reduce shear force values in beef from 5.9 N (unprocessed control) to 4.3 N (100 MPa) and 4.9 N (500 MPa; Ichinoseki and others ), the higher shear force values observed in this study were likely due to the much higher collagen content in abalone (3.5%) compared to beef (0.29% to 0.57%); Nakamura and others ).…”
Section: Resultscontrasting
confidence: 48%
“…The correlation of the collagen and shear force value or sensory tenderness has been observed in several earlier experiments but the results differ. Nakamura et al (2010) found a positive correlation between shear force and collagen content of the longissimus thoracis muscle of Japanese Black and Brown steers. Collagen characteristics were noticed as a poor indicator of meat toughness from young bulls of fifteen European breeds in the study by Christensen et al (2011).…”
Section: Discussionmentioning
confidence: 82%
“…Loins samples (1 mm × 1 mm) were fixed in glutaraldehydeparaformaldehyde in 0.1 mol/L phosphate buffer solution (pH 7.4), processed and visualized according to the reported procedure (Nakamura, Tsuneishi, Kamiya, & Yamada, 2010). Loins samples (1 mm × 1 mm) were fixed in glutaraldehydeparaformaldehyde in 0.1 mol/L phosphate buffer solution (pH 7.4), processed and visualized according to the reported procedure (Nakamura, Tsuneishi, Kamiya, & Yamada, 2010).…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
“…The loin samples from each treatment were cut transversally to the muscle fiber at the end of each allocated freezing x ageing treatments. Loins samples (1 mm × 1 mm) were fixed in glutaraldehydeparaformaldehyde in 0.1 mol/L phosphate buffer solution (pH 7.4), processed and visualized according to the reported procedure (Nakamura, Tsuneishi, Kamiya, & Yamada, 2010).…”
Section: Scanning Electron Microscopymentioning
confidence: 99%